Predictive factors of quality of life among the elderly in Iran: Application of Andersen's behavioral model - Soghra Nazari; Koorosh Kamali; Khadijeh Hajimiri (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: This study aimed to identify the quality of life (QoL) and its predictive factors based on the Andersen's behavioral model among the elderly in Iran. MATERIALS AND METHODS: A quantitative cross-sectional study was conducted on 400 people aged 60+ resident in Zanjan, Iran, in 2019. Data were collected based on the Andersen's behavioral model constructs by the questionnaires. Path analysis was used to determine both direct and indirect effects of variables and also for estimating the values of coefficients in the underpinning linear model. RESULTS: In this study, 50% of the participants were female, and 83% were married. The participant's QoL was 37.4 (9.8). The results confirmed that financial level and physical activity were the most significant predictor of the elder's QoL. Chronic diseases and activities of daily living as need factors affect the QoL of participant indirectly. CONCLUSION: The results showed that the participant's QoL was at a moderate level. Utilizing of primary health-care services was the weakest predictors of QoL. Sex, marital status, and education level were not reliable predictors of QoL in elders. Other predisposing, enabling, and need factors should be investigated to find the main determinants to improve elder's QoL.